Organic Azides 2009
DOI: 10.1002/9780470682517.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Schmidt Rearrangement Reactions with Alkyl Azides

Abstract: The sobriquet ' Schmidt reaction ' refers to a number of related processes in which hydrazoic acid or an alkyl azide reacts with an electrophile. 1 -6 The product obtained will depend on the reaction partner (carboxylic acids generate amines, aldehydes give nitriles and formamides, and ketones provide amides, respectively) but all of these reactions have certain features in common. They are the initial nucleophilic addition of the azide component to an electrophile (usually promoted by acid) eventually followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 113 publications
0
20
0
Order By: Relevance
“…[16] Ta king advantage of an intramolecular AubØ-Schmidt reaction, [17] rearrangement of 2-(2-azidoethyl)cyclobutanone using HBF 4 in Et 2 Oc ould be achieved to give three products, including the HBF 4 salt, the in situ-formed hydrolysis product, and the BF 3 complexi n9 7% combined yield (Scheme 2A). [16] Ta king advantage of an intramolecular AubØ-Schmidt reaction, [17] rearrangement of 2-(2-azidoethyl)cyclobutanone using HBF 4 in Et 2 Oc ould be achieved to give three products, including the HBF 4 salt, the in situ-formed hydrolysis product, and the BF 3 complexi n9 7% combined yield (Scheme 2A).…”
Section: Synthesis Of 7-hypoquinuclidoniumt Etrafluoroborate A[ 22mentioning
confidence: 99%
See 2 more Smart Citations
“…[16] Ta king advantage of an intramolecular AubØ-Schmidt reaction, [17] rearrangement of 2-(2-azidoethyl)cyclobutanone using HBF 4 in Et 2 Oc ould be achieved to give three products, including the HBF 4 salt, the in situ-formed hydrolysis product, and the BF 3 complexi n9 7% combined yield (Scheme 2A). [16] Ta king advantage of an intramolecular AubØ-Schmidt reaction, [17] rearrangement of 2-(2-azidoethyl)cyclobutanone using HBF 4 in Et 2 Oc ould be achieved to give three products, including the HBF 4 salt, the in situ-formed hydrolysis product, and the BF 3 complexi n9 7% combined yield (Scheme 2A).…”
Section: Synthesis Of 7-hypoquinuclidoniumt Etrafluoroborate A[ 22mentioning
confidence: 99%
“…Taking advantage of an intramolecular Aubé–Schmidt reaction, rearrangement of 2‐(2‐azidoethyl)cyclobutanone using HBF 4 in Et 2 O could be achieved to give three products, including the HBF 4 salt, the in situ‐formed hydrolysis product, and the BF 3 complex in 97 % combined yield (Scheme A). As expected, reactivity studies revealed that the twisted amide, 7‐hypoquinuclidonium tetrafluoroborate, is extremely unstable.…”
Section: Twisted Amides: New Frontiersmentioning
confidence: 99%
See 1 more Smart Citation
“…When THF was used as the solvent, a complex mixture was formed (entry 9). Besides BF 3 ⋅OEt 2 , several other acids, such as triflic acid (TfOH), TMSOTf, trifluoroacetic acid (TFA), In(OTf) 3 , Zn(OTf) 2 and BiCl 3 , were also tested for their effectiveness, and the results are listed in Table 1 as well (entries [12][13][14][15][16][17]. The optimized conditions (Table 1, entry 3) were then applied to a variety of substituted 2-(N-arylcarbamoyl)-2-iminoacetates (1b-1s), and the results are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Organic azides are versatile compounds in organic synthesis. 11 One important type of reaction organic azides can be exploited for is the Schmidt reaction, 12,13 which has proved to be useful in the synthesis of nitrogen-containing heterocycles. In the Schmidt reaction, an alkyl azide firstly reacts with an electrophile, and the thus formed intermediate then undergoes 1,2-migration accompanied by the loss of dinitrogen.…”
Section: Scheme 2 Experiments Illustrating the Substituent Effectmentioning
confidence: 99%